2018
DOI: 10.18632/oncoscience.421
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: mediators of bone diseases, protection, and therapeutics potential

Abstract: Bone remodeling is a continuous lifelong process in the repair of micro-damage to bone architecture and replacement of aging tissue in bone. A failure to such process leads to pathological destructive bone diseases such as osteoporosis, rheumatoid arthritis, and osteoarthritis. However, this active process is regulated by; osteoclasts, which are involved in the bone resorption process; osteoblasts, with involvement in the bone formation process and bone-derived endothelial cells, which promote angiogenesis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 135 publications
0
99
0
Order By: Relevance
“…Its imbalance causes bone porosity and increases the risk of fracture. The balance is controlled by bone-forming osteoblasts and bone-resorbing osteoclasts interacting with blood-vessel-forming endothelial cells [229]. There is compelling evidence that exosomes and their miR cargo play a crucial role in bone remodeling [230][231][232][233][234][235][236].…”
Section: Bone Remodeling Osteoporosis and Fracture Riskmentioning
confidence: 99%
“…Its imbalance causes bone porosity and increases the risk of fracture. The balance is controlled by bone-forming osteoblasts and bone-resorbing osteoclasts interacting with blood-vessel-forming endothelial cells [229]. There is compelling evidence that exosomes and their miR cargo play a crucial role in bone remodeling [230][231][232][233][234][235][236].…”
Section: Bone Remodeling Osteoporosis and Fracture Riskmentioning
confidence: 99%
“…Another unresolved problem is how to increase the efficiency and accuracy of cancer-specific target molecules when delivered. In depth research of extracellular vesicles, especially exosome (30–100 nm), raised the intriguing possibility that exosomal cargo may be a good way to protect target molecules integrity and to enhance the accuracy of delivery [ 2 , 3 ]. Cancer cells secrete at least 10-fold more exosomes than do normal cells, and tumor-derived exosomes (TDEs) can facilitate cell-cell communication through the transport of growth factors, chemokines, microRNAs, and other small molecules [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are part of their cargo and are potential biomarkers [ 11 ]. As exosomes carry proteins, mRNAs and miRNAs that can be transferred from donor to recipient cells via target cell membrane fusion, these vesicles have recently been recognized as important mediators of interactions between different cells [ 2 ]. In tumor microenvironment, the process described above is indispensable for the transfer of cancer-promoting cellular contents to surrounding cells, thereby accelerating cancer progression [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that bioactive molecules, such as IGF-1, TGF-β, vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), angiogenin, and IL-6 that are derived from MSCs, can support bone regeneration to a great extent [ 173 , 174 , 175 , 176 ]. Furthermore, exosomes released by MSCs have been demonstrated to have a promising effect on bone remodeling and the prevention of bone loss in vivo [ 177 , 178 ].…”
Section: Therapeutic Approach and Novel Strategiesmentioning
confidence: 99%